Integrating the evidence for a terrestrial carbon sink caused by increasing atmospheric CO2. - Walker,AP; De,Kauwe MG; Bastos,A; Belmecheri,S; Georgiou,K; Keeling,R; McMahon,SM; Medlyn,BE; Moore,DJP; Norby,RJ; Zaehle,S; Anderson-Teixeira,KJ; et al. (New Phytologist, 2020)
Atmospheric carbon dioxide concentration ([CO2 ]) is increasing, which increases leaf-scale photosynthesis and intrinsic water-use efficiency. These direct responses have the potential to increase plant growth, vegetation biomass, and soil organic matter; transferring carbon from the atmosphere into terrestrial ecosystems (a carbon sink). A substantial global terrestrial carbon sink would slow the rate of [CO2 ] increase and thus climate change. However, ecosystem CO2 -responses are complex or confounded by concurrent changes in multiple agents of global change and evidence for a [CO2 ]-driven terrestrial carbon sink can appear contradictory. Here we synthesise theory and broad, multi-disciplinary evidence for the effects of increasing [CO2 ] (iCO2) on the global terrestrial carbon sink. Evidence suggests a substantial increase in global photosynthesis since pre-industry. Established theory, supported by experiments, indicates that iCO2 is likely responsible for about half of the increase. Global carbon budgeting, atmospheric data, and forest inventories indicate a historical carbon sink, and these apparent iCO2-responses are high in comparison with experiments and theory. Plant mortality and soil carbon iCO2-responses are highly uncertain. In conclusion, a range of evidence supports a positive terrestrial carbon sink in response to iCO2, albeit with uncertain magnitude and strong suggestion of a role for additional agents of global change.